Questão racial e serviço social: uma reflexão sobre o racismo institucional e o trabalho do assistente social - Eurico, Márcia Campos (2011)
The complexity of the racial relationships in Brazil reveals the battle field in which the social service is called out to intervene, because the ethical-political project that guides social worker's professional work is bearer of a social management in the perspective of the collective fellows' emancipation. The present work is a result of the research and reflection on the institutional racism and social worker's duty. It seeks to investigate professionals' perception concerning the racism, prejudice and the racial discrimination in their everyday work, from the way the institutions are organized. One of the hypotheses is that the professional work suffers interferences of the institutional racism, which strengthens the naturalization and culpability of the black people for its major permanence in the most vulnerable layers of the brazilian society, complicating the proposition of actions that modify this reality. The research unveiled the difficulty of articulation between professional ethics and the social worker's everyday work. The racism remains as the racism from the other and the social service also produces the silence that reigns in the society regarding the need to consider the specialties of the black population. We realize that the ethical-political positioning in relation to racial matter passes through the knowledge and/or engagement in the fight by the several social movements against the discrimination, in all its forms, it being race, sexual orientation, religious choice, etc. For all that has been said, nowadays, the lack of professional commitment in relation to the social matter is not tolerable anymore, whether there's a wide debate in the society on the promotion of the racial equality - although historically the dominant groups continue trying to disqualify the collective fight - or because the professional ethical-political project of the social service, explicit in the Ethics Code of 1993 recognizes freedom as central ethical value, it proposes the uncompromising defense of the human rights, the elimination of all prejudice forms and the non discrimination as fundamental ethical principals